STUDI MORFOLOGI LEBAH PEKERJA Apis dorsata Fabr. (Hymenoptera:Apidae) AGREGASI DI SIJUNJUNG - Sari, Lidya Novita; Jasmi, Jasmi; Pratiwi, Putri (Pendidikan Biologi, 2013)
ABSTRACT  A. dorsata bees is one of the bees only growing forest region in the subtropical and tropical Asia and is not found outside of Asia . A. dorsata living in a colony , consisting of a queen bee, bees worker , and drones  bees measuving morphological characteristics of the bee is very important for bee taxonomist to put some type of bee into a particular caste , in the measurement of morphological characters of  bees worker is always selected as the sample trial because the worker bees every day activities related to the environment where the bees. In connection with that have done research on Morphology Study bees worker Apis dorsata Fabr . ( Hymenoptera : Apidae ) Sijunjung Aggregation in April- May 2013 with the aim to determine the morphology of A. dorsata worker aggregation . This research uses descriptive survey method is by way of direct collection of A. dorsata were found in the location study . than  morphometric measurements in the laboratory . From the results of research on morphological studies of worker bees Apis dorsata Fabr . ( Hymenoptera : Apidae) ) in Sijunjung aggregation is derived morphological characters of different sizes in Cu a real , Rs1 , R4 , NH , Ti , while highly significant in R1 .